Expropriation initiation of the Alava-Esquivel Palace from Spanish Law and International Law - IbazetaVilla, Hegoa (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The Álava Esquivel Palace, a property located in Vitoria-Gasteiz, is declared Basque cultural heritage. However, its owner is the Tangier City Council. Currently, the Vitorian palace is deteriorated and in danger of falling, due to non-compliance with its duties as owner of the municipality of Tangier. For this reason, this study proposes the expropriation of the property, by and for the Vitoria-Gasteiz City Council, through a unilateral expropriation and/or a lump sum agreement.